Association Between Dairy Intake and Executive Function in Chinese Children Aged 6–12 Years - Zeng, Xia; Cai, Li; Gui, Zhaohuan; Shen, Tianran; Yang, Wenhan; Chen, Qingsong; Chen, Yajun (Frontiers in Nutrition, 2022)
Association between dairy intake and executive function remains controversial, especially among children, a population with fast-developing executive functions. This study aimed to explore this topic. Additionally, we further distinguished the role of dairy intake types (full- or low-fat milk or yogurt) in this relationship. This survey included 5,138 children aged 6–12 years. Dairy intakes were assessed by validated questionnaires. Executive function was measured by the behavior rating inventory of executive function (BRIEF; Parent Version), and lower T-scores of BRIEF indices indicated superior executive function performance. Results showed that children with higher dairy intake had statistically better performance in Shift (46.58 ± 7.48 vs. 45.85 ± 7.10), Initiate (48.02 ± 8.58 vs. 47.14 ± 8.33), and Working Memory (50.69 ± 8.82 vs. 49.89 ± 8.73). In the analysis of multivariate linear regression, we found that for every one unit increase in full-fat dairy intake, T-scores for Shift (β = −0.350 (95% confidence interval [CI]: (−0.660, −0.039) and Initiate (β = −0.486 (95% CI: (−0.845, −0.127) were decreased and for every one unit increase in low-fat dairy intake, T-score for Organizations of Materials (β = −0.940 (95% CI: (−1.690, −0.189) was decreased. After distinguishing dairy into milk and yogurt, we observed that only milk intake, not yogurt, was significantly associated with better executive function performance in Shift (β = −0.390 (95% CI (−0.745, −0.035) and Initiate (β = −0.509 (95% CI (−0.917, −0.101) after adjusting for potential confounding factors. This study shows that a higher intake of dairy, irrespective of fat content, is related to better executive function performance among children aged 6–12. In addition, a significantly positive relationship between dairy intake and executive function’s indices of Shift and Initiate only was observed in milk, not in yogurt.